Well-being and mathematics achievement: What is the role of gender, instructional clarity, and parental involvement? - Wilson Fadiji, Angelina; Reddy, Vijay (Frontiers in Psychology, 2023)
Introduction The aim of the present study was to explore the relationship between satisfaction with life and mathematics achievement among a nationally representative sample of Grade 9 learners in South Africa. Methods Using the Trends in Mathematics and Science Study (TIMSS 2019) based on a sample of 20,829 learners (females = 11,067 and males = 9,719), and employing structural equation modelling (SEM), we examined the nature of the relationship between satisfaction with life and mathematics achievement, considering the role of gender, parental involvement, and instructional clarity. Results Our findings showed that satisfaction with life is positively related to mathematics achievement, but is not moderated by gender. Additionally, instructional clarity contributes to, and is a partial mediator of, the relationship between life satisfaction and mathematics achievement. This suggests that greater instructional clarity is positively associated with high achievement in mathematics, over and above the relationship with satisfaction with life. By contrast, parental involvement negatively mediates this relationship, suggesting that mathematics achievement is negatively associated with certain forms of parental involvement, such as setting time aside for homework; and checking if homework is done. Discussion Given the tested linear relationship between life satisfaction, instructional clarity and mathematics achievement, the results of the study suggest that if wellbeing is improved and existing instructional practices are constantly reviewed, mathematics scores could be positively affected. In addition, the emerging finding on the negative role of parental involvement in the hypothesised mediated relationship suggests that learners could benefit from properly tailored, and government-sponsored, afterschool tutoring.